Pengaruh Penggunaan Fintech dan Kualitas Sistem Informasi Akuntansi Terhadap Tingkat Penjualan Kopi Keliling - David Saputra Lase; Fenny Afrida; Ngiw Aman Harja (Jurnal Minfo Polgan, 2026)
This study aims to analyze the effect of the use of financial technology (fintech) and the quality of accounting information systems on the sales level of mobile coffee businesses in Medan City. This study uses a quantitative approach with a purposive sampling technique on 65 respondents who are mobile coffee business actors. Data were collected through a questionnaire that has been tested for validity and reliability, where all items were declared valid and had a Cronbach Alpha value of 0.978 which indicates very good consistency. The results show that partially the use of fintech has a positive and significant effect on the sales level with a significance value of 0.000 and a calculated t value of 3.979. The quality of the accounting information system also has a positive and significant effect on the sales level with a significance value of 0.000 and a calculated t value of 4.016. Simultaneously, both variables have a significant effect on the sales level with a calculated F value of 135.071 and a significance of 0.000. The coefficient of determination (R²) value of 0.813 indicates that 81.3% of the variation in the sales level can be explained by the use of fintech and the quality of the accounting information system. Thus, the implementation of fintech and a good accounting information system has been proven to increase operational effectiveness, expand market access, and encourage increased sales and the sustainability of MSME businesses in the digital era.